A stability result for parameter identification problems in nonlinear parabolic problems - Stanislaw Migórski (International Journal of Mathematics and Mathematical Sciences)
A sequence of identification problems of coefficients in the parabolic equation with nonlinear boundary conditions is considered. The parameter (index of an element of the sequence) appears in the cost functionals as well as boundary data. It is proved that the optimal solutions exist and that under some continuous convergence of the cost functionals and the convergence of the data, the sets of optimal solutions converge in some sense to the set of optimal solutions of the limit problem.